God, We’re Not Immigrants! A Reflection on Moving and Staying - Joel Scott (PORTAL: Journal of Multidisciplinary International Studies, 2006)
The first time we went there the guy at the front told us that we had to come back the following day, at eight in the morning, to take a number. Like a patisserie. We weren’t impressed with the idea, but to be honest we were happy to have understood him. Every successful piece of communication takes on greater significance here. Often you don’t really care what has been communicated, only that it has been communicated successfully.